Characterizing two-phase flow-induced vibration in piping structures with U-bends. (June 2022) - Bamidele, Olufemi E.; Ahmed, Wael H.; Hassan, Marwan
Highlights: Two-phase flow-induced vibration in U-bends has been experimentally investigated. Local void fraction and vibration signals were analyzed simultaneously. The maximum response was found for depend on the flow patterns. A mathematical model was proposed to predict the impact force on the U-bend. Void fraction and the slip are the key parameters in modelling the dynamic forces. Abstract: The current work investigates flow-induced vibrations for air-water two-phase passing through bends. The vibration of a 90° U-bend structure with a radius to diameter ratio of 0.4 was investigated experimentally in the vertical, horizontal and axial directions for various upstream flow patterns including bubbly, slug, wavy and annular-dispersed flows. Measurements of the local void fractions at various locations along the U-bend, the upstream piping and at the location of the vibration measurements were used to evaluate the tube vibration response. Both vibration amplitude and frequency were correlated with the two-phase flow parameters such as the superficial phase velocities, slip ratio and the mass quality. The U-bend was found to vibrate due to the redistribution of the two-phases along the flow channel creating three main geometric orientations including vertical, horizontal, and an inclination of 45 o . The vibration response of the U-bend in these three positions was investigated. The results show that the excitation forces of a two-phase flow in a piping structure are highly dependent on the flow pattern and the two-phase flow conditions upstream of the U-bend. In order to understand the complex interaction between the structure vibration and the redistribution of two-phase flow-in flow channels, a mathematical model was proposed to predict the impact force on the U- bend and verified for the slug flow pattern. The fully developed void fraction and the slip between the phases are found to be the key parameters in modelling the dynamic forces affecting the U-bends. The developed slug flow model (SFM) was found to provide an acceptable prediction of the peak impact force on the U-bend for design purposes.